Pengaruh Hubungan Kerja Kemanusiaan Terhadap Proses Pengambilan Keputusan (Satu studi pada Kantor Kecamatan malalayang Manado) - Raranta, Deky Bernad; Posumah, Jhonny Hanny; Tampi, Gustaf (JURNAL ADMINISTRASI PUBLIK, 2015)
As it known that human factors in administration (including management andorganization in the dynamic sense) holds a very important and decisive. The mostimportant and decisive, because other than humans have feelings and ratio as beingthe noblest of God's creation, is also a determinant factor, because of the "elements"of the site on the dimilki organization, such as: money, machine, material, method ofwork, time and other riches that can benefit your organizationThe activity of human relations, organization leaders trying to solve problems in worksituations and issues that impinge on his subordinate individually, so that way, theycan be excited towards more effective in an attempt to improve morale in the helpcommand in the decision-making process. Further more, Maier said that with theapproach of the huma relation, can be organised for eliminating obstacles obstacles ofcommunication, prevent misjudgments and develop constructive facet of human traitsThe issue of decision-making at the time now this joyous attention from variousparties, both from among the leaders of the Government and the company, as well asfrom scholars, the export and the students from various branches of science.Has been the fact that the activities carried out within each organization, intended toachieve the objectives of the Organization in question. And you want is all of theactivity or the activity can run smoothly and objectives can be achieved with effectiveand efficient. But often occurred obstacles in carrying out activities. This is a problemthat should be solved by the leadership of the organization. In the context of thisdecision as this develop from on leadership, a role of sagat holding a decisive inmaintaining the continuity of the activities of the Organization in order to not occurstagasi (halt)Key Words: Work, Humanitarian Relations, Decision Makin